Tradisi Lisan Kabhanti Gambusu pada Masyarakat Muna di Desa Lasunapa Kecamata Duruka Kabupaten Muna Sulawesi Tenggara (Jurusan Tradisi Lisan, Fakultas Ilmu Budaya, Univeritas Halu Oleo, 2022)
The oral tradition of Kabhanti Gambusu is being eroded by time, making it important to study to understand the meanings and values contained in the tradition of Kabhanti Gambusu. This research uses a descriptive qualitative approach with data sources obtained through informants using purposive sampling techniques. The results of the research show that the values contained in the Kabhanti Gambusu tradition are the values of togetherness, aesthetic value, ethical value, value of love, and value of advice. The value of togetherness can be found when playing Kabhanti Gambusu using musical instruments such as the oud and glass bottles as the rhythm of the Kabhanti being sung.